1992
DOI: 10.1152/jappl.1992.72.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation-perfusion relationships in the lung during head-out water immersion

Abstract: Water immersion can cause airways closure during tidal breathing, and his may result in areas of low ventilation-perfusion (VA/Q) ratios (VA/Q less than or equal to 0.1) and/or shunt and, ultimately, hypoxemia. We studied this in 12 normal males: 6 young (Y; aged 20-29 yr) with closing volume (CV) less than expiratory reserve volume (ERV), and six older (O; aged 40-54 yr) with CV greater than ERV during seated head-out immersion. Arterial and expired inert gas concentrations and dye-dilution cardiac output (Q)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 6 publications
1
27
1
1
Order By: Relevance
“…This was confirmed by Cohen et al (13) and Prefaut et al (84), but not by Derion et al (20). In the latter study, shunt measured by multiple inert gas elimination was slightly increased in older subjects (ages 40 -54 yr) but not in younger subjects (ages 20 -29 yr).…”
Section: Effects Of Immersion On Ventilation and Perfusionsupporting
confidence: 52%
See 1 more Smart Citation
“…This was confirmed by Cohen et al (13) and Prefaut et al (84), but not by Derion et al (20). In the latter study, shunt measured by multiple inert gas elimination was slightly increased in older subjects (ages 40 -54 yr) but not in younger subjects (ages 20 -29 yr).…”
Section: Effects Of Immersion On Ventilation and Perfusionsupporting
confidence: 52%
“…However, varied effects have been observed on pulmonary gas exchange. During immersion, one study indicated an increase in PA O 2 ϪPa O 2 (13), while one other observed a transient decrease, and after a few minutes of immersion, a return to baseline (20). In the presence of mild pulmonary pathology, immersion may have an additional effect: loss of an observable phase IV of the singlebreath inert gas washout curve, which is traditionally interpreted as signaling the onset of airway closure (54), which, in a group of mild asthmatic subjects, was interpreted by the investigators as evidence of airway closure throughout the entire vital capacity maneuver.…”
Section: Effects Of Immersion On Ventilation and Perfusionmentioning
confidence: 99%
“…When CV is less than ERV (usually in young individuals), during immersion V A /Q relationships are preserved. Arterial P O 2 is usually increased due to an increase in the ventilation to oxygen consumption ratio (V E /V O2 ) ratio (87). When CV exceeds ERV (common in older individuals), immersion is associated with an increase in right-to-left shunt (87) and a widening of the alveolar-arterial P O 2 difference (86).…”
Section: Circulatory Responses and Fluid Shiftsmentioning
confidence: 99%
“…During submersion, divers have increased airflow resistance (227,233,392,393) due to breathing resistance and SLL (87,369). The increased WOB is exacerbated at deeper depths as the pressure increases gas density in the lung and SCUBA gear that has to be used to breathe (227).…”
Section: Respiratory Muscle Fatigue and Trainingmentioning
confidence: 99%
“…As alterações na função respiratória são desencadeadas pela ação da pressão hidrostática de duas maneiras: primeira, um gradiente de pressão hidrostática contrabalança a força dos músculos inspiratórios e deforma a parede torácica interiormente, quando os músculos estão relaxados; e a segunda é o deslocamento sangüíneo no tórax devido ao efeito compressivo da água nos vasos sangüíneos das extremidades 2,11 . Em imersão, o centro diafragmático desloca-se cranialmente, a pressão intratorácica aumenta de 0,4 para 3,4 mmHg; a pressão transmural nos grandes vasos aumenta de 3,0 a 5,0 mmHg para 12 solo e na água após um 1 e 20 minutos de imersão (n=30) Essas informações são importantes para que o fisioterapeuta possa se embasar ao propor hidroterapia como tratamento alternativo para pacientes com patologias pulmonares.…”
Section: Discussionunclassified